Knowledge Acquisition Practices and Reading Comprehension Skills of the Learners in Hilongos South District, Leyte Division, Philippines - Ginna F Tavera; Leomarich F Casinillo (Jurnal Pendidikan Indonesia, 2020)
The main purpose of this study was to determine the knowledge acquisition practices and reading comprehension of the learners in Hilongos South District, Leyte Division, Philippines. This study adopted the descriptive-survey and correlational method of research. This method tried to explore and describe the prevailing knowledge acquisition practices obtained in a particular place or situation; the reading level of the learners in terms of prior knowledge and vocabulary, and their reading comprehension as well as the extent of relationship among the variables was portrayed. The analysis and interpretation of the data led to the following findings: the knowledge acquisition practices of learners, teachers and parents were all very satisfactory, the learners had satisfactory prior knowledge and very satisfactory vocabulary level, the reading comprehension of the learner-respondents was very satisfactory. Furthermore, there were significant relationships between knowledge acquisition practices of learners and their prior knowledge, vocabulary and knowledge acquisition practices of teachers versus vocabulary level of the learners. There were also significant relationships between prior knowledge and vocabulary to the reading comprehension of the learners.